(untitled) (CIPEEX, 2025)
Thalidomide, launched in the 1950s as a sedative and anti-emetic for pregnant women, became a milestone in clinicaltoxicology when it was associated with thousands of cases ofcongenital malformations. This episode highlighted the risksof the lack of adequate testing and strict regulation. The aim ofthis presentation is to show the impact of thalidomide ontoxicology and pharmacovigilance, highlighting how it contributed to strengthening drug safety standards. Based on a bibliographical review of articles and historical documents, data was gathered on its adverse effects, global repercussionsand changes in control mechanisms. The results indicate thatthe case led to stricter monitoring of medicines, especially in pregnant women. This incident led to the creation of stricterguidelines and the strengthening of regulatory agencies, whichnow have greater authority in assessing the safety and efficacyof drugs. Today, thalidomide is still used on a restricted basisto treat leprosy and multiple myeloma, under strict control. In conclusion, the history of thalidomide has consolidatedpharmacovigilance practices and reinforced ethics in clinicalresearch, becoming a watershed for public health.